The Influence of price value, hedonic motivation, and habit on Shopee users’ continuance intention - Alya Syifa Mu'awwanah; Btari Mariska Purwaamijaya; Syti Sarah Maesaroh (Department of Accounting, Faculty of Business, Universitas PGRI Yogyakarta, 2025)
This study addresses the underexplored mediating role of user satisfaction in sustaining Shopee users’ continuance intention amid a 17% drop in site visits by mid-2025 and reduced Q2 2024 orders. Integrating the UTAUT2 and ECM frameworks, this study examines how price value, hedonic motivation, and habit shape satisfaction and long-term usage among 260 active Shopee users in West Java, Indonesia’s province with the highest internet penetration at 82.73% (APJII, 2023). Employing a quantitative explanatory design, data were collected via a five-point Likert-scale online questionnaire and analyzed using SEM-PLS in SmartPLS 4. Findings confirm that price value and hedonic motivation fully influence continuance intention through user satisfaction, whereas habit has the strongest direct effect and partially mediates this relationship. The model yields substantial predictive power (Adjusted R² > 0.70 for both endogenous constructs). These insights urge Shopee to strengthen retention through competitive pricing, gamified experiences, and habit-forming mechanisms, thereby bolstering Indonesia’s resilience in volatile markets